The importance of food and mealtimes in dementia care : the table is set - Berg, Grethe, 1947- (Jessica Kingsley Publishers, 2006)
Mealtimes are about much more than just re-fuelling, and the importance of mealtimes in the care of people with dementia cannot be overestimated. Using her extensive experience of working with older people with dementia, Grethe Berg explains how mealtimes can be used as natural opportunities for meaningful interaction, socialising and reminiscing, and useful forums for taking part in familiar tasks. The book considers the social significance of mealtimes and their role in maintaining patients' feelings of social attachment and well-being as well as the impact of the symptoms of dementia on foo.